Identification of Early-Onset Preeclampsia-Related Genes and MicroRNAs by Bioinformatics Approaches. (August 2015) - Song, Jing; Li, Yue; An, Rui Fang
Background: Early-onset preeclampsia (EOPET), resulting in intrauterine growth restriction, has serious impact on maternal, perinatal, and neonatal livability worldwide. The current study conducted bioinformatics analyses to screen key genes and microRNAs (miRNAs) involved in EOPET and thus to explore the molecular mechanisms of EOPET. Methods: The microarray data set GSE44711 containing 8 EOPET placentas and 8 gestational age–matched controls was obtained from the Gene Expression Omnibus database. Differentially expressed genes (DEGs) were screened and subjected to gene ontology functional enrichment analysis. Then, Human Protein Reference Database was used to construct protein–protein interaction (PPI) network of DEGs. Besides, we predicted EOPET-associated miRNAs and built the miRNA regulatory network. Results: A total of 150 DEGs including 26 upregulated and 124 downregulated genes were obtained. Corticotropin releasing hormone ( CRH ) and vitronectin ( VTN ) was the most significantly upregulated and downregulated genes, respectively. The DEGs were mainly related to the biological process (BP) of pregnancy, hormone-involved process, and formation of extracellular region. Analysis of PPI network revealed that fibronectin 1( FN1 ), FBJ murine osteosarcoma viral oncogene homolog ( FOS ), CD247 molecule ( CD247 ), VTN, and interleukin 2 receptor, beta ( IL2RB ) were the top 5 DEGs with highest node degree. Furthermore, many EOPET-associated miRNAs were identified and miR-142-3p was the most significant one. Additionally, multiple miRNAs, such as miR-200b/c and miR-27a/b, were predicted to regulate the expression of several key DEGs. Conclusion: The current study identified several regulators in EOPET, which may contribute to interpret the molecular mechanism of EOPET and develop novel biomarkers and therapeutic targets for EOPET.